Perlindungan Hukum Terhadap Korban Perkosaan Dari Abortus Provocatus - I Gede Agus Surya Gunantara; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2024)
Pregnancy due to rape has a negative impact on the victim, namely physically, mentally, socially so that the victim performs abortion provocatus, but the Criminal Code does not provide exceptions regarding the act of abortion Unlike the Law of the Republic of Indonesia No. 36 of 2009 concerning Health, abortion is allowed if the requirements of the Law are met. This is certainly contrary to the reproductive rights of organs. Therefore, legal protection for rape victims is needed to protect everyone's right to legal treatment and protection. The formulation of the problem is What is the criminal law regulation regarding abortion provocatus carried out by rape victims? and What is the legal protection for rape victims from abortion provocatus? Research methods used normative legal research. The results of the discussion on criminal law regulations for rape victims from abortion provocatus are contained in Articles 299, 346, 349 of the Criminal Code and Law of the Republic of Indonesia No. 36 of 2009 concerning Health Articles 75, 76, 77, 194. It is necessary to cooperate with relevant parties to ensure that the implementation of abortion does not traumatize rape victims and can perform abortions legally, safely as permitted by law.The research method used is normative legal research. The results of the discussion regarding the regulation of criminal law against rape victims of abortion provocatus are contained in the Criminal Code Articles 299, 346, 349 and Law No. 36 of 2009 concerning Health Articles 75, 76, 77, 194. Need for cooperation of related parties to ensure the implementation of abortion does not traumatize victims of rape and can perform abortion legally, safely permitted by law.